Dissipation in microwave quantum circuits with hybrid nanowire Josephson elements - Mugnai, D.; Ranfagni, A.; Agresti, A. (Physics letters. A, 2017)
Recent experiments on hybrid Josephson junctions have made the argument a topical subject. However, a quantity which remains still unknown is the tunneling (or response) time, which is strictly connected to the role that dissipation plays in the dynamics of the complete system. A simple way for evaluating dissipation in microwave circuits, previously developed for describing the dynamics of conventional Josephson junctions, is now presented as suitable for application even to non-conventional junctions. The method is based on a stochastic model, as derived from the telegrapher's equation, and is particularly devoted to the case of junctions loaded by real transmission lines. When the load is constituted by lumped-constant circuits, a connection with the stochastic model is also maintained. The theoretical model demonstrated its ability to analyze both classically-allowed and forbidden processes, and has found a wide field of applicability, namely in all cases in which dissipative effects cannot be ignored. •Dissipative effects in Hybrid Josephson junctions (HJJ) are evaluated.•We apply a known methodology to HJJ in order to obtain the response time of the system.•We present a new theoretical result and its application to HJJ in the case of lumped-constant circuits.